Healthcare Futures: Opportunities, Challenges and Risks in a Blockchain-Driven Environment - Robert Goldberg; Peter J. Pitts; Jennifer Hinkel (Blockchain in Healthcare Today)
The integration of blockchain technology and smart contracts presents a transformative opportunity in healthcare financing by enabling the creation and trading of futures contracts based on the value of medical innovations. Traditional financial mechanisms struggle to capture the downstream savings generated by new therapies, particularly as insurers and health systems face the challenge of managing short-term costs while realizing long-term health benefits. Blockchain’s decentralized, transparent, and tamper-proof infrastructure offers a solution by providing reliable data that tracks health outcomes, cost savings, and patient behavior in real-time.